Is transverse screw fixation really necessary in PAO?—A comparative in vivo study. Issue 1 (3rd May 2021) - Leopold, Vincent J; Conrad, Juana; Hipfl, Christian; Müllner, Maximilian; Khakzad, Thilo; Perka, Carsten; Hardt, Sebastian
Abstract: The optimal fixation technique in periacetabular osteotomy (PAO) remains controversial. This study aims to assess the in vivo stability of fixation in PAO with and without the use of a transverse screw. We performed a retrospective study to analyse consecutive patients who underwent PAO between January 2015 and June 2017. Eighty four patients (93 hips) of which 79% were female were included. In 54 cases, no transverse screw was used (group 1) compared with 39 with transverse screw (group 2). Mean age was 26.5 (15–44) in group 1 and 28.4 (16–45) in group 2. Radiological parameters relevant for DDH including lateral center edge angle of Wiberg (LCEA), Tönnis angle (TA) and femoral head extrusion index (FHEI) were measured preoperatively, post-operatively and at 3-months follow-up. All patients were mobilized with the same mobilization regimen. Post-operative LCEA, TA and FHEI were improved significantly in both groups for all parameters ( P  ≤ 0.0001). Mean initial correction for LCEA ( P  = 0.753), TA ( P  = 0.083) and FHEI ( P  = 0.616) showed no significant difference between the groups. Final correction at follow-up of the respective parameters was also not significantly different between both groups for LCEA ( P  = 0.447), TA ( P  = 0.100) and FHEI ( P  = 0.270). There was no significant difference between initial and final correction for the respective parameters. Accordingly, only minimal loss of correction was measured, showing no difference between the two groups for LCEA ( P  = 0.227), TA ( P  = 0.153) and FHEI ( P  = 0.324). Transverse screw fixation is not associated with increased fragment stability in PAO. This can be taken into account by surgeons when deciding on the fixation technique of the acetabular fragment in PAO.